Transcutaneous Vagal Nerve Stimulation Alone or in Combination With Radiotherapy Stimulates Lung Tumor Infiltrating Lymphocytes But Fails to Suppress Tumor Growth - Reijmen, Eva; De Mey, Sven; Van Damme, Helena; De Ridder, Kirsten; Gevaert, Thierry; De Blay, Emmy; Bouwens, Luc; Collen, Christine; Decoster, Lore; De Couck, Marijke; Laoui, Damya; De Grève, Jacques; et al. (Frontiers in Immunology, 2021)
The combination of radiotherapy (RT) with immunotherapy represents a promising treatment modality for non-small cell lung cancer (NSCLC) patients. As only a minority of patients shows a persistent response today, a spacious optimization window remains to be explored. Previously we showed that fractionated RT can induce a local immunosuppressive profile. Based on the evolving concept of an immunomodulatory role for vagal nerve stimulation (VNS), we tested its therapeutic and immunological effects alone and in combination with fractionated RT in a preclinical-translational study. Lewis lung carcinoma-bearing C57Bl/6 mice were treated with VNS, fractionated RT or the combination while a patient cohort with locally advanced NSCLC receiving concurrent radiochemotherapy (ccRTCT) was enrolled in a clinical trial to receive either sham or effective VNS daily during their 6 weeks of ccRTCT treatment. Preclinically, VNS alone or with RT showed no therapeutic effect yet VNS alone significantly enhanced the activation profile of intratumoral CD8+ T cells by upregulating their IFN-γ and CD137 expression. In the periphery, VNS reduced the RT-mediated rise of splenic, but not blood-derived, regulatory T cells (Treg) and monocytes. In accordance, the serological levels of protumoral CXCL5 next to two Treg-attracting chemokines CCL1 and CCL22 were reduced upon VNS monotherapy. In line with our preclinical findings on the lack of immunological changes in blood circulating immune cells upon VNS, immune monitoring of the peripheral blood of VNS treated NSCLC patients (n=7) did not show any significant changes compared to ccRTCT alone. As our preclinical data do suggest that VNS intensifies the stimulatory profile of the tumor infiltrated CD8+ T cells, this favors further research into non-invasive VNS to optimize current response rates to RT-immunotherapy in lung cancer patients.